Learning subject-specific L2 terminology: The effect of medium and order of exposure - Mežek, Špela; Pecorari, Diane; Shaw, Philip; Irvine, Aileen; Malmström, Hans (English for specific purposes (New York, N.Y.), 2015)
In the globalised university environment, many university students are expected to learn subject-specific terminology in both the local language and the L2 (English) by learning from two media in two different languages: lectures in the local language and reading in L2 English. These students' bilingual learning is greatly affected by the learning strategies they employ. An experiment was designed to investigate the effects of student choice of learning media and the order of media on their learning and perception of learning of terminology in English. The results confirm that added exposure to terminology in different media, even in different languages, contributes to learning and show that, in some circumstances, learning terminology from reading may be more effective than learning it from a lecture. The results also show that students do not correctly judge their knowledge of terms learnt from different media in different languages and that they underestimate knowledge gained from reading in L2. Implications for teaching are discussed. •Students in this study learn L2 terminology from lectures in L1 and reading in L2.•The effects of their learning strategies (choice and order of media) were examined.•Added exposure to terms in different media contributes to learning.•Learning terminology from reading may be more effective than from a lecture.•Students underestimate knowledge gained from reading.